High-temperature-resistant and corrosion-resistant smelting furnace lining material and preparation process thereof
By using electromelted magnesium sand, flake graphite, nanocarbon black and phenolic resins doped with transition metal elements in the magnesium carbon furnace lining material, combined with Al2O3-SiC powder, a high temperature and corrosion-resistant smelting furnace lining material is formed, and magnesium carbon is solved. The carbon consumption and corrosion problems of furnace lining materials in high temperature and corrosive environments improve oxidation and slag resistance, extend service life and reduce energy consumption.
Patent Information
- Application Number
- CN202411310140.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
AI Technical Summary
The existing magnesium carbon furnace lining materials have problems such as high carbon consumption, high thermal conductivity and serious erosion in high temperature and corrosive environments, which affects their service life.
Using electromelted magnesium sand, flake graphite, nanocarbon black, phenolic resin doped with transition metal elements and Al2O3-SiC powder, a high temperature and corrosion-resistant smelting furnace lining material is formed through a specific preparation process, and nanocarbon black and flake graphite are used. The composite carbon source and transition metal oxides in the phenolic resin form a one-dimensional nanocarbon structure, combining Al2O3-SiC powder to improve antioxidant and slag corrosion resistance.
It significantly improves the oxidation resistance, pyrolysis and thermal shock resistance of the furnace lining materials, extends the service life and reduces energy consumption.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of furnace lining materials, and in particular to a high-temperature-resistant and corrosion-resistant smelting furnace lining material and a preparation process thereof. Background Art
[0002] When the smelting furnace is smelting, the appropriate lining material is selected according to the temperature, chemical corrosion, mechanical wear and other conditions in the smelting furnace body. In the high temperature and corrosive furnace environment, the lining material must have high temperature resistance and corrosion resistance. The service life of the lining material is affected by many factors, such as the oxidation of the lining material, the effect of thermal stress, metal erosion and penetration, etc. Therefore, improving the anti-oxidation and anti-slag erosion properties of the lining material is of great significance to extending the service life of the lining material. Magnesium carbon lining material is a widely used lining material. It is composed of magnesia aggregate, graphite, antioxidants, binders, etc. It has the advantages of high corrosion resistance, spalling resistance, thermal shock resistance, etc. However, the carbon consumption of this lining material is large, the thermal conductivity is high, and the energy consumption and erosion are increased, so it needs to be improved to a certain extent. Summary of the invention
[0003] The object of the present invention is to provide a high temperature and corrosion resistant smelting furnace lining material and a preparation process thereof, so as to solve the problems existing in the background technology.
[0004] To achieve the above object, the present invention provides the following technical scheme: a high temperature and corrosion resistant smelting furnace lining material, which is made of the following raw materials in weight percentage: 55-60% of fused magnesia coarse particles, 30-35% of fused magnesia fine particles, 2-3% of flake graphite, 0.5-0.9% of nano carbon black, 1-2% of phenolic resin doped with transition metal elements and 1-3% of Al2O3-SiC powder, wherein the transition metal elements include at least one of Ti, Co, Ni, Fe or Cr, and the Al2O3-SiC powder is prepared by the following steps: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and sealing them in a ceramic crucible, wherein the C / SiO2 mass ratio is 3-4; 2) placing the ceramic crucible in a high temperature resistance furnace and heating it to 1500-1600°C, and keeping it warm for 2-3h; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder.
[0005] As a preferred embodiment of the present technical solution, the coarse particles of the fused magnesia have a particle size of 3-4 mm, and the fine particles of the fused magnesia have a particle size of 1-2 mm.
[0006] As a preferred embodiment of the present technical solution, the particle size of the flake graphite is 0.1-0.2 mm, and the particle size of the nano carbon black is 5-10 nm.
[0007] As a preferred embodiment of the present technical solution, when the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique, and then the sol precursor is compounded with the phenolic resin.
[0008] The present invention also provides a preparation process of a high temperature resistant and corrosion resistant smelting furnace lining material, which comprises the following steps: 1) dry mixing coarse fused magnesia particles in a mixer for 3-5 minutes; 2) heating liquid phenolic resin to 60-70°C, adding it into the mixer and mixing it for 5-6 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 4-5 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, putting it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0009] Beneficial effects of the present invention:
[0010] 1. The composite carbon source of nano carbon black and flake graphite is used as the lining material, and the performance of the smelting lining material obtained is better than that of the lining material using flake graphite alone as the carbon source.
[0011] 2. Doping transition metal elements into phenolic resin can catalyze the cracking of the resin to form a one-dimensional nanocarbon structure (such as carbon nanotubes, carbon nanofibers and other graphitized carbon), thereby increasing the residual carbon rate of the resin and the oxidation resistance of the pyrolysis secondary carbon.
[0012] 3. The A12O3-SiC powder synthesized by carbon thermal reduction method was added to the furnace lining material. It was found that the introduction of A12O3-SiC composite powder can significantly improve the corrosion resistance and penetration resistance of the low-temperature furnace lining material to oxidizing slag, and also improve its antioxidant performance to a certain extent. DETAILED DESCRIPTION
[0013] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0014] Example 1
[0015] The high temperature and corrosion resistant smelting furnace lining material is made of the following raw materials in percentage by weight: 55% of coarse fused magnesia particles, 35% of fine fused magnesia particles, 2% of flake graphite, 0.5% of nano carbon black, 2% of phenolic resin doped with transition metal elements and 3% of Al2O3-SiC powder, wherein the particle size of the coarse fused magnesia particles is 3 mm, the particle size of the fine fused magnesia particles is 2 mm, the particle size of the flake graphite is 0.1 mm, the particle size of the nano carbon black is 5 nm, and the transition metal elements include Ti and Ni. The preparation steps of Al2O3-SiC powder are as follows: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and putting them into a ceramic crucible and sealing them, wherein the mass ratio of C / SiO2 is 3; 2) placing the ceramic crucible in a high temperature resistance furnace and heating it to 1500°C, and keeping it warm for 3 hours; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder.
[0016] When the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique and then compounded with the phenolic resin.
[0017] The preparation process of a high-temperature and corrosion-resistant smelting furnace lining material comprises the following steps: 1) dry-mixing coarse fused magnesia particles in a mixer for 5 minutes; 2) heating liquid phenolic resin to 70°C, adding it into the mixer and mixing it for 6 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 4 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, placing it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0018] The smelting furnace lining material obtained in this embodiment has an apparent porosity of 4.3%, a cold crushing strength of 51 MPa, a thermal rupture modulus of 4.5 MPa, a slag penetration depth of 2.1 mm, and a thermal shock resistance of 12 cycles.
[0019] Example 2
[0020] The high temperature and corrosion resistant smelting furnace lining material is made of the following raw materials in percentage by weight: 60% of fused magnesia coarse particles, 30% of fused magnesia fine particles, 3% of flake graphite, 0.9% of nano carbon black, 1% of phenolic resin doped with transition metal elements and 1% of Al2O3-SiC powder, the particle size of the fused magnesia coarse particles is 4 mm, the particle size of the fused magnesia fine particles is 1 mm, the particle size of the flake graphite is 0.1 mm, the particle size of the nano carbon black is 10 nm, the transition metal element is Ti, and the Al2O3-SiC powder preparation steps are: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and putting them into a ceramic crucible and sealing them, with a C / SiO2 mass ratio of 4; 2) putting the ceramic crucible into a high temperature resistance furnace and heating it to 1600°C, and keeping it warm for 2 hours; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder. When the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique and then compounded with the phenolic resin.
[0021] The preparation process of a high-temperature and corrosion-resistant smelting furnace lining material comprises the following steps: 1) dry-mixing coarse fused magnesia particles in a mixer for 3 minutes; 2) heating liquid phenolic resin to 60°C, adding it into the mixer and mixing it for 5 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 5 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, placing it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0022] The smelting furnace lining material obtained in this embodiment has an apparent porosity of 4.5%, a cold crushing strength of 56 MPa, a thermal rupture modulus of 4.7 MPa, a slag penetration depth of 1.9 mm, and a thermal shock resistance of 14 cycles.
[0023] Example 3
[0024] The high temperature and corrosion resistant smelting furnace lining material is made of the following raw materials in percentage by weight: 58% of coarse fused magnesia particles, 33% of fine fused magnesia particles, 2.5% of flake graphite, 0.6% of nano carbon black, 1.5% of phenolic resin doped with transition metal elements and 2% of Al2O3-SiC powder, wherein the particle size of the coarse fused magnesia particles is 3 mm, the particle size of the fine fused magnesia particles is 1 mm, the particle size of the flake graphite is 0.1 mm, the particle size of the nano carbon black is 6 nm, and the transition metal elements include Ti, Co, Ni and Fe. The preparation steps of Al2O3-SiC powder are as follows: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and sealing them in a ceramic crucible, wherein the C / SiO2 mass ratio is 4; 2) placing the ceramic crucible in a high temperature resistance furnace and heating it to 1550°C, and keeping it warm for 2.5 hours; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder. When the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique and then compounded with the phenolic resin.
[0025] The preparation process of a high-temperature and corrosion-resistant smelting furnace lining material comprises the following steps: 1) dry-mixing coarse fused magnesia particles in a mixer for 4 minutes; 2) heating liquid phenolic resin to 65°C, adding it into the mixer and mixing it for 5.5 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 5 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, placing it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0026] The smelting furnace lining material obtained in this embodiment has an apparent porosity of 3.8%, a cold crushing strength of 48 MPa, a thermal rupture modulus of 4.1 MPa, a slag penetration depth of 2.5 mm, and a thermal shock resistance of 10 cycles.
[0027] Example 4
[0028] The high temperature and corrosion resistant smelting furnace lining material is made of the following raw materials in percentage by weight: 57% of fused magnesia coarse particles, 31% of fused magnesia fine particles, 2% of flake graphite, 0.8% of nano carbon black, 1.5% of phenolic resin doped with transition metal elements and 1% of Al2O3-SiC powder, the particle size of the fused magnesia coarse particles is 3.5mm, the particle size of the fused magnesia fine particles is 1mm, the particle size of the flake graphite is 0.2mm, the particle size of the nano carbon black is 8nm, and the transition metal elements include Ti, Co, Ni, Fe and Cr. The Al2O3-SiC powder preparation steps are: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and putting them into a ceramic crucible and sealing them, with a C / SiO2 mass ratio of 3.5; 2) putting the ceramic crucible into a high temperature resistance furnace and heating it to 1600°C, and keeping it warm for 3h; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder. When the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique and then compounded with the phenolic resin.
[0029] The preparation process of a high-temperature and corrosion-resistant smelting furnace lining material comprises the following steps: 1) dry-mixing coarse fused magnesia particles in a mixer for 4 minutes; 2) heating liquid phenolic resin to 70°C, adding it into the mixer and mixing it for 6 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 4 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, placing it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0030] The smelting furnace lining material obtained in this embodiment has an apparent porosity of 4.1%, a cold crushing strength of 46 MPa, a thermal rupture modulus of 3.8 MPa, a slag penetration depth of 2.7 mm, and a thermal shock resistance of 11 cycles.
[0031] Example 5
[0032] The high temperature and corrosion resistant smelting furnace lining material is made of the following raw materials in percentage by weight: 60% of fused magnesia coarse particles, 35% of fused magnesia fine particles, 2% of flake graphite, 0.5% of nano carbon black, 2% of phenolic resin doped with transition metal elements and 1.5% of Al2O3-SiC powder, the particle size of the fused magnesia coarse particles is 4mm, the particle size of the fused magnesia fine particles is 1.5mm, the particle size of the flake graphite is 0.2mm, the particle size of the nano carbon black is 6nm, the transition metal elements include Ti, and Cr, and the Al2O3-SiC powder preparation steps are: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and putting them into a ceramic crucible and sealing them, with a C / SiO2 mass ratio of 4; 2) putting the ceramic crucible into a high temperature resistance furnace and heating it to 1580°C, and keeping it warm for 3h; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder.
[0033] When the phenolic resin is doped with a transition metal element, a sol precursor of a transition metal oxide is prepared by a sol-gel technique and then compounded with the phenolic resin.
[0034] The preparation process of a high-temperature and corrosion-resistant smelting furnace lining material comprises the following steps: 1) dry-mixing coarse fused magnesia particles in a mixer for 5 minutes; 2) heating liquid phenolic resin to 66°C, adding it into the mixer and mixing it for 6 minutes; 3) adding fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mixing them for 5 minutes; 4) pressing the mixture into a shape at a pressure of 120MPa, curing it at 180°C for 10 hours, placing it into a sagger, burying petroleum coke, carbonizing it at 1400°C for 5 hours, and obtaining the smelting furnace lining material after cooling.
[0035] The smelting furnace lining material obtained in this embodiment has an apparent porosity of 4.6%, a cold crushing strength of 42 MPa, a thermal rupture modulus of 4.1 MPa, a slag penetration depth of 2.02 mm, and a thermal shock resistance of 12 cycles.
Claims
1. A high temperature and corrosion resistant smelting furnace lining material, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 55-60% of coarse fused magnesia particles, 30-35% of fine fused magnesia particles, 2-3% of flake graphite, 0.5-0.9% of nano carbon black, 1-2% of phenolic resin doped with transition metal elements and 1-3% of Al2O3-SiC powder, wherein the transition metal elements include at least one of Ti, Co, Ni, Fe or Cr. The preparation steps of Al2O3-SiC powder are as follows: 1) crushing, mixing and drying clay, silicon oxide, carbon black and catalyst, and putting them into a ceramic crucible and sealing them, wherein the mass ratio of C / SiO2 is 3-4; 2) putting the ceramic crucible into a high-temperature resistance furnace and heating it to 1500-1600°C, and keeping it warm for 2-3h; 3) taking out the ceramic crucible and cooling it to room temperature, taking out the materials, grinding and sieving them to obtain powder.
2. The high temperature and corrosion resistant smelting furnace lining material according to claim 1, characterized in that: The coarse particles of the fused magnesia have a particle size of 3-4 mm, and the fine particles of the fused magnesia have a particle size of 1-2 mm.
3. The high temperature and corrosion resistant smelting furnace lining material according to claim 1, characterized in that: The particle size of the flake graphite is 0.1-0.2 mm, and the particle size of the nano carbon black is 5-10 nm.
4. The high temperature and corrosion resistant smelting furnace lining material according to claim 1, characterized in that: When the phenolic resin is doped with transition metal elements, a sol precursor of transition metal oxide is prepared by sol-gel technology, and then the sol precursor is compounded with the phenolic resin.
5. A process for preparing a high temperature and corrosion resistant smelting furnace lining material, characterized in that: The following steps are involved: 1) dry-mix the coarse fused magnesia particles in a mixer for 3-5 minutes; 2) heat the liquid phenolic resin to 60-70°C, add it into the mixer and mix it for 5-6 minutes; 3) add the fine fused magnesia particles, flake graphite, nano carbon black and Al2O3-SiC powder and mix them for 4-5 minutes; 4) press the mixture into a shape at a pressure of 120MPa, cure it at 180°C for 10 hours, put it into a sagger, bury it with petroleum coke, carbonize it at 1400°C for 5 hours, and obtain the smelting furnace lining material after cooling.
Citation Information
Patent Citations
Method of introducing silicon carbide matrix synthetic material to improve thermal shock resistance of ultra-low carbon magnesia-carbon material
CN108440004A
Method for introducing silicon carbide-based synthetic material to improve slag resistance of ultralow carbon-magnesium-carbon material
CN108585796A
Low-carbon ultra-low-carbon carbon-containing refractory material containing in-situ peeled two-dimensional micro-nano graphite flake phenolic resin composition, and preparation method thereof
CN110240466A
Preparation method for improving performance of MgO-C brick through modified phenolic resin
CN116003143A
Ultralow-carbon magnesia carbon brick and preparation method thereof
CN117164366A
Cited By
Nano ladle magnesia carbon brick and preparation process thereof
CN120329009A
Magnesia material for alloy smelting and preparation method and application thereof
CN121470929A